The Merdeka Belajar-based Digital Literacy Skill of Indonesian Language Courses as The Effective Mean to Improve Islamic Characters at Economic Faculty of Universitas Muhammadiyah Semarang - Yustinah Yustinah (Journal of Islamic Studies and Society, 2023)
This research is themed on Merdeka Belajar-based Digital Literacy Skill for Indonesian course as an effective facility to improve the Islamic character of Economic Faculty students of Universitas Muhammadiyah Semarang. This research analyzed the Merdeka belajar, self-directed learning–based digital literacy skills in an Indonesian language course, starting from the plan, implementation, and evaluation. The improved Islamic characters of the students were based on honesty (sidiq), trust (amanah), sharing (tabligh), and intelligence (fathonah). The research subjects were the management and accounting students of an Indonesian language course. This descriptive statistic research collected the data by distributing a questionnaire on Google Forms. The results showed the planning aspect obtained a percentage of 59.9%; implementation (57.25%); and evaluation (62.3%). The results showed that the self-directed learning-based digital literacy in the Indonesian language course effectively improved the Islamic characters of the Economic Faculty students of Universitas Muhammadiyah Semarang.